Study of effect of microsecond pulsed electric fields on threshold area of HeLa Cells - Adon, Mohamad Nazib; Dalimin, M. Noh; Abdul Jamill, Muhammad Mahadi; Mohd Kassim, Norazan; Hamdan, Sallehhuddin (2012)
Microsecond pulse electric field (IlSPEF) application development substantially affected the development of research process including controlling cell functions by using pulses of electrical fields to create pores through a cellular membrane causes cell lysis and apoptosis commonly known as electroporation. Here we demonstrate the influence of the IlSPEF on the threshold area (TA) of human cervical cancer cells (HeLa) membrane. The electric field for IlSPEF is 3kV/cm while the pulse interval is lOOms. The pulse length and the number of pulses were fixed at lOllS and 5, respectively. While the cultured skin cells are placed in 9 mm-gap EP electrode chamber for allowing real time observation of membrane permeability changes and cellular physiology. In order to initiate higher cell viability rate, high transfection efficiency, lower sample contamination and smaller Joule heating effect the modification of EP chamber need to be done which can be controlled by pH scale, temperature and humidity. The experiment using high pulse electrical field with simply repetitive pulses shows the threshold area of cell membrane was decreasing gradually to 44.59Ilm, and is settled within hundreds of second. We found that the threshold area of cells membrane was affected when exposed to high voltage pulse electric field. The dependence of the threshold area on the HeLa cell membrane might be associated with the electrical impedance of the plasma membrane that begins to fluctuate after the application of a certain level of IlSPEF.